2012
DOI: 10.1160/th12-03-0153
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the platelet transcriptome in chronic kidney disease

Abstract: Bleeding and thrombotic disorders are major complications affecting patients with chronic kidney disease (CKD). Exposure of circulating platelets to uraemic toxins and contact with artificial surfaces during dialysis induce platelet abnormalities and alter the platelet proteome. We hypothesised that these changes may be subsequent to changes in the composition and/or regulation of the platelet transcriptome. In this study, we investigated the circulating platelets of 10 CKD patients (i.e. five chronic haemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…2,29,30 A miR-223 reporter construct was created by inserting a sequence complementary to hsa-miR-223 in the Xba1 site of pRL-CMV vector (Promega, Madison, WI), downstream of the Renilla luciferase (Rluc) reporter gene. pRL-CMV-39UTR Ephrin A1 (EFNA1) and pRL-CMV-39UTR F-box/WD repeat-containing protein 7 (FBXW7) constructs were engineered by amplifying and cloning their 39UTR element downstream of the Rluc reporter gene in pRL-CMV vector.…”
Section: Reporter Gene Activity Assaysmentioning
confidence: 99%
“…2,29,30 A miR-223 reporter construct was created by inserting a sequence complementary to hsa-miR-223 in the Xba1 site of pRL-CMV vector (Promega, Madison, WI), downstream of the Renilla luciferase (Rluc) reporter gene. pRL-CMV-39UTR Ephrin A1 (EFNA1) and pRL-CMV-39UTR F-box/WD repeat-containing protein 7 (FBXW7) constructs were engineered by amplifying and cloning their 39UTR element downstream of the Rluc reporter gene in pRL-CMV vector.…”
Section: Reporter Gene Activity Assaysmentioning
confidence: 99%
“…These molecules in platelets may come from different sources, such as those inherited from megakaryocytes, those absorbed from the plasma, or those generated de novo. With regard to de novo synthesis of molecules in platelets, although platelets are anucleate, they express significant amounts of RNA, including mRNAs (e.g., premature and mature RNA), structural and catalytic RNAs (e.g., ribosomal and tRNA), regulatory RNAs (e.g., microRNA), and noncoding RNA (e.g., anti-sense RNA) (90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). More recently, it also was revealed that platelets contain all of the molecular machinery to translate mRNA into proteins, and they have the ability to transfer RNA to recipient cells where it can regulate cellular function (101-104).…”
Section: Platelet Transcriptomicsmentioning
confidence: 99%
“…Examination of RNA expression patterns in platelets has been used to identify biomarkers of disease, explain genetically or environmentally induced alterations in platelet function, and determine if genes are conserved between humans and mice. [1][2][3][4][5][6][7][8][9][10][11][12][13] The past decade has also revealed that platelets can translate mRNA into protein or transfer RNA to recipient cells where it regulates functional processes. [14][15][16][17] Because platelets are anucleate, transcriptional production of RNA (with the notable exception of mitochondria-derived transcripts) presumably occurs exclusively in the megakaryocyte.…”
Section: Introductionmentioning
confidence: 99%